Design And Implementation Of Accounting And Financial Reporting System At Paud Zhen Xin & Bimbel - Widijaya Widijaya; Joelyn Veronica (Universitas Internasional Batam, 2023)
Most Micro, Small, and Medium Enterprises (MSMEs) do not use accounting records in managing their business, due to a lack of knowledge and awareness in applying accounting records in their business. The application of a clear accounting system can help MSMEs to develop properly, and carry out their operations effectively and efficiently, helping MSMEs to make the best decisions. One example of MSMEs is Paud Zhen Xin & Bimbel which still uses the cash basis method of recording and only records its income in a book, so there is a need for a reliable accounting recording system to be able to create information about financial reports that are accurate, fast and relevant to make it easier for owners to make decisions. decisions related to company operations based on financial report data. Data collection uses interview and observation techniques with MSME owners in the period July to December 2022. System design uses Microsoft Access which is capable of inputting transactions such as cash receipts and disbursement transactions, and recording adjusting journals. This accounting system will display financial reports such as a statement of financial position, income statement, statement of changes in equity, reports on cash transactions, general ledger, and income statement per student.